2012
DOI: 10.1063/1.4742279
|View full text |Cite
|
Sign up to set email alerts
|

"Edge illumination" in X-ray Phase Contrast Imaging

Abstract: Although early demonstration dates back to the mid-sixties, x-ray phase-contrast imaging (XPCI) became hugely popular in the mid-90s, thanks to the advent of 3rd generation synchrotron facilities. Its ability to reveal object features that had so far been considered invisible to x-rays immediately suggested great potential for applications across the life and the physical sciences, and an increasing number of groups worldwide started experimenting with it. At that time, it looked like a synchrotron facility wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…proportional to the first derivative of the phase shift) XPCI images are obtained in this way, just like the ones obtained on one side of the reflectivity curve of an analyser crystal [26]. Although in our case the differential nature is due to the convolution of "half" a free-space propagation profile with the pixel response function [27,28], it can be shown that, by optimizing beam thickness and sample-to-detector distance so that comparable phase sensitivity is achieved, results effectively equivalent to analyser based imaging are obtained [13].…”
Section: Methodsmentioning
confidence: 54%
“…proportional to the first derivative of the phase shift) XPCI images are obtained in this way, just like the ones obtained on one side of the reflectivity curve of an analyser crystal [26]. Although in our case the differential nature is due to the convolution of "half" a free-space propagation profile with the pixel response function [27,28], it can be shown that, by optimizing beam thickness and sample-to-detector distance so that comparable phase sensitivity is achieved, results effectively equivalent to analyser based imaging are obtained [13].…”
Section: Methodsmentioning
confidence: 54%